Transformational leadership, work motivation, and teacher performance: Evidence from the Sula Islands, Indonesia - Fitra Nita Nur; Edi Sugiono; Hasanudin Hasanudin (Journal of Economics and Business Letters, 2026)
This study aims to examine the effect of school principal transformational leadership and work motivation on teacher performance at SMA Negeri 1 Kepulauan Sula, a remote insular school context that remains underexplored in Indonesian educational leadership research. Using an explanatory research approach, data were collected from 48 teachers through a saturated sampling technique and a 1–5 Likert-scale questionnaire, then analyzed with SmartPLS 4. Results show that transformational leadership significantly affects teacher performance (β = 0.502) and work motivation (β = 0.886), while work motivation significantly affects teacher performance (β = 0.486), jointly explaining 92.2% of its variance. This topic was chosen because senior high schools in geographically isolated regions face distinct leadership and motivational challenges rarely addressed in prior studies. The novelty lies in testing this model within a remote insular context to help reconcile inconsistent prior findings. It is recommended that principals strengthen transformational leadership and design context-specific strategies to sustain teacher motivation.   Keywords: transformational leadership; work motivation; teacher performance; school principal.